â€œCloud computing an overviewâ€ - S, Shilpashree.; R. Patil, Renuka; C, Parvathi (International Journal of Engineering and Technology, 2018)
Cloud Computing is one of the emerging technologies in all fields and is called as the type of computing relayed on the internet. The main functions of Cloud Computing are hosting and delivering of various software and services using the internet. Depending on the demands and requirements of the user, the cloud computing affords the main computational resources to users as service. The main computational resources are larger storage space, server with high performance, various operating systems for various platforms and Network. The demand for these resources by the user is increasing day by day with the main drawback of security and is considered as a very serious problem in cloud computing. This paper has surveyed the various concepts related to cloud computing such as, the architecture, types and models for deployment, applications, advantages and disadvantages. The main goal of this paper is to provide a better knowledge about the cloud computing and its issues in the research on various domains. Â Â